Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the value of [tex]\( x \)[/tex] using algebra tiles to solve the equation [tex]\( x + 1 = -x + (-5) \)[/tex], we will proceed step-by-step.
### Step 1: Setup the Equation with Algebra Tiles
- On the left side of the equation, we have [tex]\( x + 1 \)[/tex].
- On the right side, we have [tex]\( -x + (-5) \)[/tex].
### Step 2: Combine Like Terms
The goal is to isolate the variable [tex]\( x \)[/tex]. We can start by adding [tex]\( x \)[/tex] to both sides of the equation to eliminate [tex]\( -x \)[/tex] from the right side.
So,
[tex]\[ x + x + 1 = -x + x + (-5) \][/tex]
This simplifies to:
[tex]\[ 2x + 1 = -5 \][/tex]
### Step 3: Isolate the Variable [tex]\( x \)[/tex]
Next, we need to isolate [tex]\( 2x \)[/tex]. Subtract 1 from both sides of the equation:
[tex]\[ 2x + 1 - 1 = -5 - 1 \][/tex]
This simplifies to:
[tex]\[ 2x = -6 \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Finally, divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ \frac{2x}{2} = \frac{-6}{2} \][/tex]
This simplifies to:
[tex]\[ x = -3 \][/tex]
### Conclusion
So, the value of [tex]\( x \)[/tex] when using algebra tiles to solve the equation [tex]\( x + 1 = -x + (-5) \)[/tex] is [tex]\(\boxed{-3}\)[/tex].
This solution matches with one of our given choices:
- [tex]\( x = -1 \)[/tex]
- [tex]\( x = 1 \)[/tex]
- [tex]\( x = 2 \)[/tex]
- [tex]\( x = -3 \)[/tex]
### Step 1: Setup the Equation with Algebra Tiles
- On the left side of the equation, we have [tex]\( x + 1 \)[/tex].
- On the right side, we have [tex]\( -x + (-5) \)[/tex].
### Step 2: Combine Like Terms
The goal is to isolate the variable [tex]\( x \)[/tex]. We can start by adding [tex]\( x \)[/tex] to both sides of the equation to eliminate [tex]\( -x \)[/tex] from the right side.
So,
[tex]\[ x + x + 1 = -x + x + (-5) \][/tex]
This simplifies to:
[tex]\[ 2x + 1 = -5 \][/tex]
### Step 3: Isolate the Variable [tex]\( x \)[/tex]
Next, we need to isolate [tex]\( 2x \)[/tex]. Subtract 1 from both sides of the equation:
[tex]\[ 2x + 1 - 1 = -5 - 1 \][/tex]
This simplifies to:
[tex]\[ 2x = -6 \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Finally, divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ \frac{2x}{2} = \frac{-6}{2} \][/tex]
This simplifies to:
[tex]\[ x = -3 \][/tex]
### Conclusion
So, the value of [tex]\( x \)[/tex] when using algebra tiles to solve the equation [tex]\( x + 1 = -x + (-5) \)[/tex] is [tex]\(\boxed{-3}\)[/tex].
This solution matches with one of our given choices:
- [tex]\( x = -1 \)[/tex]
- [tex]\( x = 1 \)[/tex]
- [tex]\( x = 2 \)[/tex]
- [tex]\( x = -3 \)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.